Role of the immune system in regeneration and its dynamic interplay with adult stem cells. (March 2019) - Abnave, Prasad; Ghigo, Eric
Abstract: The immune system plays an indispensable role in the process of tissue regeneration following damage as well as during homeostasis. Inflammation and immune cell recruitment are signs of early onset injury. At the wound site, immune cells not only help to clear debris but also secrete numerous signalling molecules that induce appropriate cell proliferation and differentiation programmes essential for successful regeneration. However, the immune system does not always perform a complementary role in regeneration and several reports have suggested that increased inflammation can inhibit the regeneration process. Successful regeneration requires a balanced immune cell response, with the recruitment of accurately polarised immune cells in an appropriate quantity. The regulatory interactions of the immune system with regeneration are not unidirectional. Stem cells, as key players in regeneration, can also modulate the immune system in several ways to facilitate regeneration. In this review, we will focus on recent research demonstrating the key role of immune system in the regeneration process as well as the immunomodulatory effects of stem cells. Finally, we propose that research investigating the interplay between the immune system and stem cells within highly regenerating animals can benefit the identification of the key interactions and molecules required for successful regeneration.